Penerapan Model Project-Based Learning (PjBL) Berbasis Ekologi dalam Pembelajaran Teks Prosedur di SMP - Aldi Dwi Saputra; Rini Dwi Haryati; Edy Suryanto; Raheni Suhita; Muhammad Rohmadi (Pusat riset dan Inovasi Nasional, 2025)
Indonesian language learning at the junior high school level requires students not only to comprehend texts but also to apply them in real-life contexts. One of the essential text types to be taught is the procedural text, which aims to develop students’ instructional abilities as well as their sequential and systematic thinking skills. This study aims to describe the implementation of an ecology-based Project-Based Learning (PjBL) model in teaching procedural texts in junior high school. The research employed a qualitative method with a case study approach. Data collection techniques included observation, documentation, and interviews. The researcher and the teacher collaborated to discuss the application of the ecology-based PjBL model in teaching procedural texts to seventh-grade students at SMP Negeri 4 Surakarta. The researcher then observed the procedural text learning activities carried out by the teacher using the PjBL model and conducted an evaluation of the model's implementation, student engagement, and the effectiveness of the activities in achieving learning objectives. The results indicated that the implementation of the ecology-based PjBL model effectively increased students’ active participation, enhanced their understanding of procedural text concepts, and fostered early awareness of waste management and environmental conservation.